STUDI OPTIMASI PRODUKSI ASSOCIATED GAS DAN PEMANFAATANNYA DI LAPANGAN - Dwiherjuno, Budhianto
Solution gas or commonly called as associated gas is a gas which dissolved in the oil and liberated from oil when the reservoir pressure drop and reach the bubble point pressure as a result of the production process. Generally because of the amount of associated gas which produced to the surface are small or not economically viable for sell, the associated gas is dumped without being used by burning (flaring). But in the global warming era, associated gas flaring has received a lot of attention, especially because environmental aspect. Therefore, the idea began to emerge such as the utilization of associated gas to meet the electricity needs of field operations and others. And then, reservoir with driving mechanism of solution gas expansion (solution gas drive) also has its own uniqueness. One of them is the formation of a secondary gas cap. Secondary gas cap is the solution gas that accumulates to the top of the oil to form a cap due to the gravity. The formation of a secondary gas cap in the reservoir also affects the associated gas production optimization strategy. Lack of studies on the field development strategies for utilization of associated gas, encourage authors to conduct this study. Bottomhole pressure and wells location sensitivity performed to determine what the appropriate strategies to be applied. Scenario with the most optimum production profile (both oil and associated gas production) will then be converted into electricity production profile which can be generated and given an overview utilization to satisfy the electricity requirement of field operations, especially for artificial lift.